1986
DOI: 10.1042/bj2390213
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the phosphorylated night form and dephosphorylated day form of phosphoenolpyruvate carboxylase from Bryophyllum fedtschenkoi

Abstract: Phosphoenolpyruvate carboxylase of Bryophyllum fedtschenkoi was shown to exist in two forms: a night form, which is phosphorylated and has low sensitivity to inhibition by malate, and a day form, which is dephosphorylated and 10 times more sensitive to malate. The day and night forms of the enzyme were purified retaining their distinct malate sensitivities and phosphorylation states. The purified enzymes contained a major protein (subunit Mr 112,000) and a minor protein (subunit Mr 123,000). The two polypeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
96
2
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 24 publications
1
96
2
3
Order By: Relevance
“…During the subsequent light period, the malic acid is decarboxylated in the cytosol to provide CO # for fixation via ribulose-1,5-bisphosphate carboxylase\ oxygenase (Rubisco) under low photorespiratory conditions in the chloroplast. Work with M. crystallinum has been central to our understanding of the differential regulation of PEPC over the day-night cycle (Winter, 1982), now known to be regulated in part by phosphorylation (Nimmo et al, 1986 ;Li & Chollet, 1994 ;Cushman & Bohnert, 1997). Finally, at the molecular level, changes in gene expression, which are synchronized with, and generate, a developmental pattern, are accelerated by stress.…”
Section:  mentioning
confidence: 99%
“…During the subsequent light period, the malic acid is decarboxylated in the cytosol to provide CO # for fixation via ribulose-1,5-bisphosphate carboxylase\ oxygenase (Rubisco) under low photorespiratory conditions in the chloroplast. Work with M. crystallinum has been central to our understanding of the differential regulation of PEPC over the day-night cycle (Winter, 1982), now known to be regulated in part by phosphorylation (Nimmo et al, 1986 ;Li & Chollet, 1994 ;Cushman & Bohnert, 1997). Finally, at the molecular level, changes in gene expression, which are synchronized with, and generate, a developmental pattern, are accelerated by stress.…”
Section:  mentioning
confidence: 99%
“…This velocity test is both sensitive and rapid, and thus possesses advantages over the classical malate-sensitivity test, especially when a low phosphorylation state of PEPC and high proteolytic and protein phosphatase activities are to be found in crude extracts. As described by Nimmo et al (1986), partia1 proteolysis of Bryophyllum fedtschenkoi PEPC results in changes in malate sensitivity not related to the phosphorylation process, thereby leading to a misinterpretation of the results. Using this velocity test, we showed that the pH 8:pH 7.3 PEPC activity ratio decreases b y 27% during the first 4 d of germination (Fig.…”
Section: Dlscusslonmentioning
confidence: 99%
“…For example, PEP has been observed to increase transiently upon illumination of maize leaves (6) (19,29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Since PEP carboxylase is a cytosolic enzyme it is unlikely to be controlled in the same way by light as are the chloroplastic enzymes, although factors such as the pH of the cytosol might change in response to light (18). In CAM plants regulation by light may occur through a dimer-tetramer conversion, possibly mediated by Mg2+ (30), or by phosphorylation of the enzyme (19), with the result that the active enzyme from darkened leaves has a lower Km (PEP) and is rendered much less sensitive to inhibition by malate (19,29,30).…”
mentioning
confidence: 99%